The Effect Of Self-Control And Conformity On Student Consumptive Behavior Of Ar-Rahman Sma Medan Year 2020 - Candra Wijaya, Mardianto, Muhammad Aji Prasetia (LPPPIPublishing, 2021)
Existence is the relationship between self-control and conformity to students' consumptive behavior. Where students who have low self-control coupled with the existence social influence in the student environment will cause students to behave consumptively by buying goods that are not following what is needed. Some of the problems in this study are consumptive behavior in high adolescents, the influence of the school environment on consumptive behavior, low self-control in students, student emotions are generally not stable, Students as consumers are still less realistic in determining their needs with the desires of the product to be purchased. In research, is using methods quantified. The result of the research is that there is a significant influence between self-control and the consumptive behavior of students. This means that the better or positive the student's self-control, the lower the student will be to behave consumptively. There is also a significant influence between conformity on the consumptive behavior of students. Which is the lower the conformity or social influence of the environment, the lower the students will be to carry out consumptive behavior, and it is hoped that students who are young to be able to adapt themselves to normative and informational social influences so that they are not easily influenced by existing social conditions in his environment. Self-control and conformity have a significant influence on the consumptive behavior of students of SMA Ar Rahman Medan. This means positive self-control and conformity the students have, the less often these students behave consumptively and vice versa.